MICROHABITAT PREFERENCE AND SEASONALITY OF GILL MONOGENEANS IN NILE TILAPIA REARED IN SOUTHERN BRAZIL - Laterça Martins, Mauricio (2014)
Few studies have been done to evaluate the monogenean microhabitat preference. This study evaluated the monogenean distribution among different gill arches of Nile tilapia Oreochromis niloticus and seasonality. A total of 89 fish were captured in a pond located in Chapecó, Santa Catarina, for parasitological analysis. After fish euthanasia, the gill arches were removed, separated from the most external to the most internal and named as I, II, III and IV. Transparency, pH, oxygen, temperature, alkalinity, conductivity, ammonia, iron, orthophosphate, sulfide, nitrite and nitrate of water pond were measured. In spring 2008 the mean abundances of the monogeneans (Scutogyrus longicornis, Cychlidogyrus sclerosus, C. thurstonae and C. tilapiae) in the arches I, II, III and IV were, respectively, 11.45, 14.45, 13.8, 13.15, in summer 2008 theywere 13.12, 12.25, 14.94, 21.53, in summer 2009 they were 2.75, 3.25, 2.45, 2.45, in autumn 2009 they were 13.44, 18.78, 11.78, 9.22 and in winter 2009 they were 0.35, 0.5, 0.3, 0.5. Monogenean preference for microhabitat in the gills of farmed Nile Tilapia was not observed. A significant increase of parasites in spring and summer 2008 and autumn 2009 was observed. The highest number of parasites coincided with seasons of high water temperature. The lack of microhabitat preference among the gill arches suggest homogenous distribution of parasites combined with water quality parameters.